Burning down the house : the end of juvenile prison - Bernstein, Nell. (New York : The New Press, 2014)
"When teenagers scuffle during a basketball game, they are typically benched. But when Will got into it on the court, he and his rival were sprayed in the face at close range by a chemical similar to Mace, denied a shower for twenty-four hours, and then locked in solitary confinement for a month. One in three American children will be arrested by the time they are twenty-three, and many will spend time locked inside horrific detention centers that defy everything we know about how to rehabilitate young offenders. In a clear-eyed indictment of the juvenile justice system run amok, award-winning journalist Nell Bernstein shows that there is no right way to lock up a child. The very act of isolation denies delinquent children the thing that is most essential to their growth and rehabilitation: positive relationships with caring adults. Bernstein introduces us to youth across the nation who have suffered violence and psychological torture at the hands of the state. She presents these youths all as fully realized people, not victims. As they describe in their own voices their fight to maintain their humanity and protect their individuality in environments that would deny both, these young people offer a hopeful alternative to the doomed effort to reform a system that should only be dismantled. Burning Down the House is a clarion call to shut down our nation's brutal and counterproductive juvenile prisons and bring our children home."--
The time is at hand -- Teenage wasteland. Inside juvenile prison ; Birth of an abomination : the juvenile prison in the nineteenth century ; Other people's children ; The rise of the super-predator and the decline of the rehabilitative ideal ; The fist and the boot : physical abuse in juvenile prisons ; An open secret : sexual abuse behind bars ; The Hole : solitary confinement of juveniles ; "Hurt people hurt people" : trauma and incarceration ; The things they carry : juvenile reentry -- Burning down the house. A new wave of reform ; A better mousetrap : the therapeutic prison ; Only connect : rehabilitation happens in the context of relationship ; Connection in action : transforming juvenile justice ; The real recidivism problem : one hundred years of reform and relapse at the Arthur G. Dozier School for Boys ; Against reform : beyond the juvenile prison.
Includes bibliographical references.
Keywords: Juvenile justice, Administration of -- United States; Juvenile delinquency -- United States; Juvenile courts -- United States